2021
DOI: 10.1007/978-3-030-85947-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Lower Bounds for the Query Complexity of Equilibria in Lipschitz Games

Abstract: Nearly a decade ago, Azrieli and Shmaya introduced the class of λ-Lipschitz games in which every player's payoff function is λ-Lipschitz with respect to the actions of the other players. They showed that such games admit -approximate pure Nash equilibria for certain settings of and λ. They left open, however, the question of how hard it is to find such an equilibrium. In this work, we develop a query-efficient reduction from more general games to Lipschitz games. We use this reduction to show a query lower bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Furthermore, Hadiji et al [2023] recently investigated the first-order query complexity of computing ǫ-Nash equilibria in m × m two-player zero-sum games (cf. [Goldberg and Katzman, 2023, Fearnley and Savani, 2016, Babichenko, 2016, Fearnley et al, 2015, Maiti et al, 2023). They showed that Ω(m) (first-order) queries are needed when ǫ = 0, and roughly Ω(log( 1 mǫ )) when ǫ = O( 1 m 4 ), thereby leaving a substantial gap with the upper bound of O( log m ǫ ) attained via OMWU.…”
Section: Further Related Workmentioning
confidence: 99%
“…Furthermore, Hadiji et al [2023] recently investigated the first-order query complexity of computing ǫ-Nash equilibria in m × m two-player zero-sum games (cf. [Goldberg and Katzman, 2023, Fearnley and Savani, 2016, Babichenko, 2016, Fearnley et al, 2015, Maiti et al, 2023). They showed that Ω(m) (first-order) queries are needed when ǫ = 0, and roughly Ω(log( 1 mǫ )) when ǫ = O( 1 m 4 ), thereby leaving a substantial gap with the upper bound of O( log m ǫ ) attained via OMWU.…”
Section: Further Related Workmentioning
confidence: 99%